The shaping of narrative in Polybius - Miltsios, Nikos, 1980- (Berlin : De Gruyter, 2013)
In his attempt to explain Rome's rise to world power, Polybius composed a carefully structured narrative. Yet, despite its sophistication, Polybius' narrative artistry has received little scholarly attention. This study is the first book-length narratological analysis of the Histories. It contributes to our understanding of its content and purpose by unveiling the narrative strategies employed by Polybius in shaping his intriguing story.
Frontmatter -- Acknowledgments -- Contents -- Introduction -- 1. Well begun is half done -- 2. The narrative of the prokataskeue -- 3. Temporal strategies -- 4. Focalization and interpretation -- 5. The Polybian narrator -- Conclusions -- Bibliography -- Index Locorum -- General Index.
Includes bibliographical references and indexes.
Print version record.
Online resource; title from PDF title page (ebrary, viewed January 2, 2014).
English.
eBooks on EBSCOhost
Keywords: Polybius; Historiae (Polybius); Polybius -- v200-v120; Historians -- Rome; Rome -- Historiography; Historiens -- Rome; HISTORY -- Ancient -- Rome; Historians; Historiography; Rome (Empire); Erzähltechnik; Narrative; Polybius